Fuzzy Reasoning House of Risk to Manage Supply Chain Risk in Wooden Toys Industries - Widya Nurcahayanty Tanjung; Selma Himawan; Syarif Hidayat; Endang Ripmiatin; Selvy Sekar Asti; Ratu Siti Khodijah; Saaras Ayu Atikah (International Journal of Supply Chain Management, 2019)
An unexpected event in the supply chain will disturb material flow and activities in the whole. The occurrence of such interference would have caused losses at time and cost. In order to anticipate this situation, it needs proper supply chain risk management. Research was done in wooden toy industry case study which has wide marketing range. Fuzzy Reasoning House of Risk (FRHOR) are used to solved the problem. FRHOR is combination of fuzzy reasoning risk assessment model and house of risk. House of Risk Method is used to identify the most potential risk agents, while the fuzzy reasoning risk assessment model is used to determine the risk severity by risk agents. Based on the analysis, it is found that risk agent stock out of the product is the most potential risk agent. To reduce the impact, recommended mitigation strategies that can be used for stock out product risk agents in werehouse are flexible supply base, safety stock, internal coordination, as well as create and control production schedules.